62.3k views
4 votes
Jerome solved the equation below by graphing.

log2(x) + log2(x-2) = 3
Which of the following shows the correct system of equations and solution?

Jerome solved the equation below by graphing. log2(x) + log2(x-2) = 3 Which of the-example-1
User Balu
by
6.3k points

2 Answers

1 vote

Answer:

B. x = 4

Explanation:

I can't speak to the first part of this question, as I don't totally have context for what they're asking, but we can solve for x using one of the laws of logarithms, namely:


\log_bm+\log_bn=\log_bmn

Using this law, we can combine and rewrite our initial equation as


\log_2(x\cdot(x-2))=3\\\log_2(x^2-2x)=3

Remember that logarithms are simply another way of writing exponents. The logarithm
\log_28=3 is just another way of writing the fact
2^3=8. Keeping that in mind, we can express our logarithm in terms of exponents as


\log_2(x^2-2x)=3\rightarrow2^3=x^2-2x

2³ = 8, so we can replace the left side of our equation with 8 to get


8 = x^2-2x

Moving the 8 to the other side:


0=x^2-2x-8

We can now factor the expression on the right to find solutions for x:


0=(x-4)(x+2)\\x=4, -2

The only option which agrees with our solution is B.

User Bielas
by
6.5k points
3 votes

Answer:

The answer is:


y_1=(\log x)/(\log 2)+(\log (x-2))/(\log 2)\ ,\ y_2=3\ ,\ x=4

Explanation:

We are given a logarithmic expression as:


\log_2 x+log_2 (x-2)=3

As we know that:


\log_a x=(\log x)/(\log a)

Hence, we get the logarithmic expression as follows:


(\log x)/(\log 2)+(\log (x-2))/(\log 2)=3

We know that we can get the system of equations as follows:


y_1=(\log x)/(\log 2)+(\log (x-2))/(\log 2)

and


y_2=3

Hence, when we plot the graph for this system of equations we see that the point of intersection of the graph is: (4,3)

Hence, the solution is the x-value of the point of intersection of the two equations.

Hence, x=4 is the solution.

Hence, the correct option is:


y_1=(\log x)/(\log 2)+(\log (x-2))/(\log 2)\ ,\ y_2=3\ ,\ x=4

Jerome solved the equation below by graphing. log2(x) + log2(x-2) = 3 Which of the-example-1
User Utkonos
by
6.5k points